2008
DOI: 10.2174/1874276900802010014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anaemia Among Pregnant women in Nigeria

Abstract: Abstract:To assess the prevalence and risk factors of anaemia in pregnancy and recommend a cut-off value for antenatal women in developing countries, a cross sectional study was carried in the University of Port Harcourt Teaching Hospital, Port Harcourt, a 523 bed tertiary health care institution in Nigeria. 1371 apparently healthy asymptomatic pregnant women visiting the antenatal clinic for the first time were enrolled for the study. Another 60 age-matched non-pregnant apparently healthy women served as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 24 publications
(21 reference statements)
7
53
4
Order By: Relevance
“…These values are higher than the present figure of 21.7%. Data on Anaemia prevalence in Nigeria have been dominated by figures from pregnant women [24], preschool age children [25][26][27], and critically ill children [28]. However, the study by Olayemi and Halim [29] among apparently healthy adults Nigerians documented Anaemia prevalence of 51.8%, a value higher than the present figure of 21.7%.…”
Section: Discussionmentioning
confidence: 53%
“…These values are higher than the present figure of 21.7%. Data on Anaemia prevalence in Nigeria have been dominated by figures from pregnant women [24], preschool age children [25][26][27], and critically ill children [28]. However, the study by Olayemi and Halim [29] among apparently healthy adults Nigerians documented Anaemia prevalence of 51.8%, a value higher than the present figure of 21.7%.…”
Section: Discussionmentioning
confidence: 53%
“…18,19 And lower in women attended to antenatal clinic at hospital of Potro Novo-Cape Verde, Benin 38.8% and in other two studies in Nigeria 23.2% and 29%, 16.6% in Northwest Ethiopia. 15,[20][21][22] Interestingly, this finding is higher to the overall prevalence found among pregnant women than other studies in the Middle East and North Africa, 40.08 % in Algeria, 26.2% in Bahraini, 27.1% in East Anatolian Province, Turkey, Jordan (34.7%) and (39%) in Makkah, Saudi Arabia. [23][24][25][26][27] There are many reasons to explain this variation.…”
Section: Discussionmentioning
confidence: 88%
“…7 Other study in Nigeria noted that majority of the women were 30-34 years (34.1%) followed by of 25-18 years (33.5%), 20-24 years (14.8%), 35-39 years (12.9%) and rest were in other age group which was different from our study. 8 One of the study of Kalyobia showed that 30% women were 18-25 years, 50% were 25-32 years and 20% were more than 32 years of age. 9 Majority 148 (37.0%) of the women had secondary level education followed by primary level education 121 (30.3%), higher secondary 55 (13.8%), illiterate 43 (10.8%) and 33 (8.3%) had graduate level education in this study.…”
Section: Discussionmentioning
confidence: 99%